Implementasi Kebijakan Peraturan Bupati Sekadau Nomor 52 Tahun 2022 Pada Sistem CMS (Cash Management System) Di Kabupaten Sekadau - Theodora Gading; Sri Haryaningsih; Pardi Pardi (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This research aims to describe and analyze the implementation of Sekadau Regent Regulation Number 52 of 2022 concerning the Standard Operational Procedure (SOP) for Village Financial Management and Non-Cash Transactions in Bokak Sebumbun Village and Merapi Village, Sekadau Hilir Sub-district, Sekadau Regency. The policy is part of an effort to enhance transparency and accountability in village fund management, where the implemented Cash Management System (CMS) allows village financial transactions to be automatically recorded and monitored by all interested parties. The research method used is a descriptive qualitative approach. The results indicate that this policy successfully increased the transparency of village fund management; however, there are still significant challenges related to technology infrastructure and the human resource capacity of the village officials. Limited internet access and the low level of understanding among village officials in operating the digital CMS system hinder the effectiveness of this policy. Furthermore, public accessibility to transaction reports and oversight of village funds needs to be improved to ensure that the policy genuinely aligns with the priorities and needs of the village community.